Harriet [videorecording (DVD)] - Nettles, Jennifer; Alwyn, Joe; Erivo, Cynthia, 1987-; Monáe, Janelle (Universal, 2020)
Based on the thrilling and inspirational life of an iconic American freedom fighter, the movie tells the extraordinary tale of Harriet Tubman's escape from slavery and transformation into one of America's greatest heroes. Her courage, ingenuity, and tenacity freed hundreds of slaves and changed the course of history.